The Provision of Lend Based on Collateral in the Form of Inherited Objects on Behalf of the Heirs in Relation to the Principle of Legal Certainty - Alensia*, Melysa Putri; Lunandi, Yenny Yuniawaty (Universitas Syiah Kuala, 2023)
Financial limitations to make ends meet, allow everyone to borrow some money from individuals and banking institutions. In granting credit to debtors, the bank requires the debtor to provide collateral. In practice, there is land and/or buildings which are objects of inheritance on behalf of the testator which are used as collateral when applying for credit to the bank. This study aims to understand and examine legal certainty for banks as creditors if the debtor uses the object of inheritance as collateral in applying for credit. In this study the authors used a legal research method that used a normative juridical research type, namely research that was intended to conduct a study of the application of rules or norms in positive law. The data source used by the author in this study is secondary data obtained from library research. The results of the research show that collateral is an important requirement in granting credit. Collateral is the bank's belief in the ability and ability of the debtor to pay off his debt obligations according to the agreement, so that the bank should have strict criteria for receiving guarantees from the debtor. behind the first name on behalf of the heirs in order to provide legal certainty for the bank as a creditor.